The relationship between readiness and teachers` competency towards creativity in teaching among trainee teachers - Sulaiman, Tajularipin; Hamzah, Siti Nurkhuzaimah; Abdul Rahim, Suzieleez Syrene (International Association of Computer Science and Information Technology Press, 2017)
Readiness is the ability of an individual to begin teaching. Competence is the efficiency in the execution of an instruction to be more efficient. Creativity is the thinking process that encourages a person to generate new ideas for the implementation of teaching. The objective of this study is to identify the level of readiness and competency of trainee teachers towards creativity in teaching and to identify the relationship between readiness and competency of teachers with creativity in teaching. The design of this research is a descriptive and correlational study using a questionnaire as the research instrument. A total of 100 trainee teachers were involved as respondents in this study. The findings showed that the level of readiness, competency and creativity in teaching of trainee teachers were 4.13 for readiness, 4.01 for competence, and 3.99 for creativity in teaching. The findings also showed that there is a significant positive relationship between readiness and competency with creativity in teaching among trainee teachers.